Foreign entry liberalization and export quality: evidence from China - Hou, Xinyu; Shi, Yingying; Sun, Puyang (Blackwell Publishing Inc., 2020)
This paper examines the impact of foreign entry deregulation in China on the export price and quality of manufacturing firms through input-output linkage. We create a unique dataset describing the extent of regulatory control over foreign entry across approximately 900 industries covering all primary, manufacturing and services sectors. Results suggest foreign entry deregulation encourages firms to improve product quality and increase export prices. Deregulation in the manufacturing sectors has more impact on downstream export price and quality, compared with services sectors. Moreover, firms having larger imported inputs benefit more from foreign entry deregulation. These effects are robust to alternative specifications.